Mathematics Communication: Translation of Elementary Students' Idea - Gusti Firda Khairunnisa; Mohammad Archi Maulyda; Anas Ma'ruf Annizar; Lailin Hijriani; Muhammad Sa'duddien Khair (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Communication is an essential ability for every human being. In this study, the focus of communication was on students' mathematical communication. Mathematical communication is a person's ability to express their thoughts and is responsible for listening, interpreting, asking, and interpreting ideas from one to another to solve problems. This study aimed to describe the mathematical communication of Sombron Elementary School students in solving mathematical problems. This type of research is qualitative descriptive research. The research subjects were 23 students in class VI Sombron Elementary School. Three issues were selected for more in-depth analysis because they represented three categories: high, medium, and low ability students. Based on the subjects' works, the students could not communicate their mathematical ideas well yet. The most common communication error was a mistake in changing the word problem into a settlement model form. Based on the results and discussions that have been carried out with three different subjects, high ability student (ST), moderate ability student (SS), and low ability student (SR) of Sombron Elementary School at class VI, it can be concluded that ST and SS understand the meaning of the problem given and they know what was asked from the issue, but they did not use a correct symbol while writing their idea. ST and SS also made some mistakes in using mathematics symbols.